Same Size Doesn't Fit All: Insights from research on listening skills at the University of the South Pacific (USP) - Chand, Rajni K. (International Review of Research in Open and Distributed Learning, 2007)
Listening skills research has tended to focus on strategy use in classrooms and on theory and practice of second language (L2) teachers. This study examined the teachers’ and learners’ perceptions of listening skills in non-classroom learning situations. Five (n = 5) study skills teachers and 19 former learners in a distance study skills course at the University of the South Pacific (USP) were interviewed for this study. The interviews with the study skills teachers sought their expectations of their learners’ listening strategies, their views about the learners they taught, and the skills their learners used for listening. Former learners were similarly questioned about their perceptions of listening strategies they were taught and used. Data was collected and managed using NVivo, a computer assisted qualitative data analysis software. Besides revealing strategies that distance learners reported using their learning listening skills, the study identified a number of differences in views presented by researchers and L2 teachers, as well as differences in perceptions on listening skills between L2 teachers and L2 learners. The paper concludes that there exists a discrepancy between research and the practice of researchers, L2 teachers, and L2 learners on what works. The author also recommends further research in this area is needed, because research examining classroom-based learning situations will likely not apply to, nor fully inform, distance learning contexts.